Revisiting the Functional Properties of Self-Efficacy: A Dynamic Perspective. (September 2013) - Yeo, Gillian B.; Neal, Andrew
This paper is a response to Bandura's 2012 Guest Editorial, which defends the functional properties of self-efficacy by criticizing published studies that have demonstrated a negative relationship between self-efficacy and performance at the within-person level of analysis. We focus on the theoretical and methodological criticisms that Bandura has made in relation to our (Yeo & Neal) 2006 piece that examined the dynamic relationship between self-efficacy and performance across levels of analysis and specificity. In doing so, we explain the importance of designing and analyzing studies involving self-efficacy at the within-person level of analysis. We then demonstrate how the concept of resource allocation can explain the co-existence of positive and negative dynamic self-efficacy effects across the between- and within-person levels of analysis. We acknowledge the great strides that researchers have made in understanding the complex and dynamic processes involving self-efficacy and encourage researchers to continue this collective effort.